(untitled) (JBN (Jurnal Bedah Nasional), 2026)
ABSTRACT INTRODUCTION: The clinical importance of ankylosis in children is concerning with its massive effect and disturbance on the mandibular growth causing deformity apart from the limited mouth opening. Trauma (neglected or abandoned condylar or subcondylar fracture) is the most common cause of bony and fibrous ankylosis. History, physical examination and radiographical examination of each patient with ankylosis of temporomandibular joint is mandatory in arriving to a final diagnosis, severity, involvement of adjacent structures and ultimately to plan the treatment. CASE PRESENTATION: A seventeen years old male presented with her family seeking solution for a severely limited mouth opening. From the history, the child has suffered from height fall at the age of 8 years old. He had complained from swelling and pain near the ear, treated by analgesics, gradually subsided and neglected. This limitation affects on feeding and had an impact on the child’s health, seeking for management for the condition became mandatory. Clinical examination, radiographical examination is prepared in beside that ethical approval with full discussion with the parents done. DISCUSSION: Patients with ankylosis are considered as serious problem. Not only because it is rare, but it also affects the growth and development of the one’s mandible as the center growth of mandible occurs at the condyles, it’s not just because of ankylosis. Surgeons should keep in their minds that well experienced anesthetist is important; also extension of the ankylosed bone with amount of cutting is important and reankylosis as a complication must be avoided. CONCLUSION: The surgeons agree with the statement that success in the preventing reankylosis after condylectomy. Its primarily refers to the early postoperative physiotherapy, maintained on a long term. Keywords: temporomandibular joint, condylectomy, mandibular hypoplasia